The Influence of Individual and Environmental Factors on Small Business Performance of Briquettes In Bangunharjo Village, Bantul Regency - Syikhristani Syikhristani; Jamhari Jamhari; Dwidjono Hadi Darwanto (Agro Ekonomi, 2018)
This study aims to: (1) acknowledge the application level of the individual factor and work environment to the employee of the coconut shell briquette small business in Bangunharjo Village, Bantul Regency, (2) acknowledge the performance level of the employee of the coconut shell briquette small business in Bangunharjo Village, Bantul Regency, (3) acknowledge the effectiveness of the individual factor and work environment toward the employee’s performance of the coconut shell briquette small business in Bangunharjo Village, Bantul Regency. The location and the sample of the research are determined in purpose based on the certain consideration and criteria through a case study. The method used in this study comprises of two independent variables and one dependent variable. The number of respondent taken are 31 people consisting of business owner and employee. The questionnaire technique being used is questionnaire with likert scale measurement 1-5 from attitude strongly disagree to strongly agree, assisted Statistical Product and Service Solutions (SPSS) program version 24 in order to obtain the descriptive data analysis, the correlation of person product moment, and double linear regression with 5% significancy range. The result of the analysis reveals: (1) the level of application of individual factors and the work environment for employees are in a good category; (2) the measurement through the employee's performance is good; (3) Individual factor and work environment both have a significant positive effect on employee's performance, this is proven by the discovery of adjusted R squared value that is 0.727 on the determination coefficient.